TANGGUNG JAWAB PIHAK PENGANGKUT ATAS KETERLAMBATAN PENDISTRIBUSIAN LOGISTIK PEMILU TAHUN 2024 DI KABUPATEN SAMBAS - NIM. A1012211004, IHZA KASURYO (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract In order to make the election successful, election logistics are needed so that the voting process can run smoothly. To distribute the 2024 election logistics from each province to each city/district, the KPU-RI gives authority to the Provincial KPU to choose a transportation service company to distribute the 2024 election logistics to each district/city. This was also done by the West Kalimantan Provincial KPU by appointing PT. Karunia Jasa Angkutan as a transportation service company in distributing the 2024 election logistics to each district/city in West Kalimantan Province. The distribution of the 2024 election logistics is made in the form of a 2024 Election Logistics Delivery Contract Agreement between the West Kalimantan Provincial Election Commission (KPU) and PT. Karunia Jasa Angkutan. During the distribution of the 2024 election logistics from the West Kalimantan Provincial KPU warehouse to the Sambas Regency KPU warehouse using a truck belonging to PT. Karunia Jasa Angkutan experienced a delay from the predetermined schedule because the truck owned by PT. Karunia Jasa Angkutan broke down in the middle of the trip and could not be repaired by the driver. However, in reality, PT. Karunia Jasa Angkutan avoided being responsible to the West Kalimantan Provincial KPU for the delay in the distribution of 2024 Election logistics to the Sambas Regency KPU warehouse. The formulation of the problem in this study is: